PENGARUH PEMBERIAN LIMBAH SINGKONG DAN MINERAL MIKRO ORGANIK TERHADAP KECERNAAN LEMAK DAN TOTAL DIGESTIBLE NUTRIENT PADA KAMBING PERANAKAN ETAWA JANTAN - Geovani Silva, Muhtarudin, Liman, dan Rudy Sutrisna (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
The purpose of this study was to determine the effect of cassava waste and organic micro minerals on fat digestibility and TDN (Total Digestible Nutrient) in Ettawa crossbreed goat. This research was conducted on 11-25 November 2018 at Gisting Atas District, Blok 18, Gisting Subdistrict, Tanggamus Regency, Lampung Province. The material used was 12 male Ettawa crossbreed goat with varied body weights. This study used a randomized block design consisted of 4 treatments and 3 replications. Grouping based on body weight is U1 (13-15 kg) U2 (15-17 kg), and U3 (17-25 kg). The research treatment consisted of R0 (control ration), R1 (fermented feed ingredients), R2 (R1 + cassava leaves) and R3 (R2 + Organic Micro Minerals). The results showed that the highest crude fat digestibility was in R0 (95.00%) and the highest TDN in R3 (68.63%) but the results of the variance analysis showed that the treatment ration had no effect on fat digestibility and TDN (P >0.05). Keywords: Cassava waste, Ettawa crossbreed, Digestibility, Organic micro minerals